Can gestational exercise have a positive effect on cognitive functions resulting from brain injury? A rat study - Dilek, Mustafa; Orallar, Hayriye; Bozat, Gokce; Kabakus, Nimet; Cetinkaya, Ayhan; Dilek, Gamze; Karakas, Fatma; Erkocoglu, Mustafa; Onal, Ali Can; Yilmaz, Fahri (EXPERIMENTAL BIOMEDICAL RESEARCH, 2018)
Aim: The effects of gestational exercise on potential pathological conditions is not known yet. Therefore, in the present study, it was aimed to evaluate the effects of forced running exercise on LPS-induced brain damage in pregnant rats. Method: Pregnant females in the experimental group were forced to exercise 30 min daily for five days a week. Lipopolysaccharide (LPS) induced brain injury model was created by administering 500 µg/kg body weight of LPS on gestational days 18 and 19. To evaluate injury histopathologically, brain tissues were fixed at the postnatal day seven through transcardial perfusion (n=4 pups/group). When the remaining pups reached 30-day of age, Morris water maze test (MWM) was performed to assess memory and learning, open filed (OP) and elevated plus maze (EPM) for testing anxiety, and Porsolt test (PT) for evaluating depression. The groups were defined as brain injury group (BI, n=13) and exercise+brain injury group (E+BI, n=7). Results: The results obtained from MWM test indicated that animals found the platform in a shorter duration and distance at the day five compared to the day three. However, there was no significant difference between the groups. No significant difference was found in OP test regarding the distance traveled, time spent at the margins, movement at the center and the time spent as immobile. However, in the EPM test, the offspring at the BI group displayed higher mobility and increased number of entry to the open arms compared to the E+BI groups (p=0.01). There was no significant difference regarding mobility duration and total distance traveled in the PT test. Conclusion: In the present study, we tested the impact of gestational exercise using the brain injury model. The results of the EPM test suggests that the gestational exercise can suppress the stress factors in the pregnant females with brain injury leading to the prevention of hyperactivity-induced negative learning behavior.